กิจกรรมการเรียนรู้ภูมิศาสตร์ทวีปเอเชีย โดยใช้เกมเป็นฐาน เพื่อพัฒนาทักษะการคิดวิเคราะห์สู่การเป็นพลเมืองโลกของนักเรียนชั้นมัธยมศึกษาปีที่ 1 เครือข่ายชาติตระการ 1 - สมสนิท, ภาณุวัฒน์; ปัญญาวุธตระกูล, วศิน; ศรีพันธ์, อัจฉรา (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 5 No 1 (2568): มกราคม – เมษายน 2568, 2025)
บทความวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาสภาพปัจจุบันของการจัดการเรียนรู้ เรื่อง ภูมิศาสตร์ทวีปเอเชีย ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 เครือข่ายชาติตระการ 1 2) เพื่อพัฒนากิจกรรมการเรียนรู้ภูมิศาสตร์ทวีปเอเชีย โดยใช้เกมเป็นฐาน เพื่อพัฒนาทักษะการคิดวิเคราะห์สู่การเป็นพลเมืองโลกของนักเรียนชั้นมัธยมศึกษาปีที่ 1กลุ่มเป้าหมาย 1) ครูโรงเรียนขยายโอกาส กลุ่มเครือข่ายโรงเรียนอำเภอชาติตระการ 1  สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาพิษณุโลก เขต 3 จำนวน 4 โรงเรียน ปีการศึกษา 2567 ด้วยการเลือกแบบเจาะจงตามคุณสมบัติที่กำหนด จำนวน 4 คน 2) นักเรียนชั้นมัธยมศึกษาปีที่ 1 โรงเรียนบ้านห้วยท้องฟานโรงเรียนขยายโอกาสกลุ่มเครือข่ายโรงเรียนอำเภอชาติตระการ 1 สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาพิษณุโลก เขต 3 ปีการศึกษา 2567 ด้วยการเลือกแบบเจาะจงตามคุณสมบัติที่กำหนด จำนวน 11 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ 1) แบบสัมภาษณ์สำหรับครูผู้สอน เรื่อง ภูมิศาสตร์ทวีปเอเชีย ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 2) คู่มือกิจกรรมการเรียนรู้ภูมิศาสตร์ทวีปเอเชีย โดยใช้เกมเป็นฐาน ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 และ 3) แบบประเมินทักษะการคิดวิเคราะห์ การสังเกตพฤติกรรม และการสัมภาษณ์ค่าสถิติที่ใช้ในการวิจัย ได้แก่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า 1) สภาพปัจจุบันของการจัดการเรียนรู้ของครูผู้สอนเรื่องภูมิศาสตร์ทวีปเอเชีย ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 เครือข่ายชาติตระการ 1 พบว่า เนื้อหาของหลักสูตรวิชาสังคม ศาสนาและวัฒนธรรมในปัจจุบันมีความเหมาะสมกับนักเรียนชั้นมัธยมศึกษาปีที่ 1 เป็นการสร้างพื้นฐานที่สำคัญต่อการเรียนรู้และการเติบโตของผู้เรียนในอนาคต ด้านการจัดการเรียนการสอน พบว่า ครูผู้สอนควรใช้วิธีการจัดการเรียนรู้ที่หลากหลาย และนำเอาสื่อการสอนมาใช้ในการจัดการเรียนรู้ให้เหมาะสมกับเนื้อหา ด้านการวัดผลประเมินผลการเรียนรู้ พบว่า ควรใช้เครื่องมือที่หลากหลาย เพื่อให้ครูสามารถเข้าใจถึงระดับความรู้และทักษะของนักเรียน และด้านอุปสรรคในการจัดการเรียนรู้ พบว่า นักเรียนขาดสมาธิและความสนใจในบทเรียน เนื่องจากมีเนื้อหาที่มากและผู้เรียนไม่เห็นภาพที่ชัดเจน 2) ผลการพัฒนากิจกรรมการเรียนรู้ภูมิศาสตร์ทวีปเอเชีย โดยใช้เกมเป็นฐาน เพื่อพัฒนาทักษะการคิดวิเคราะห์สู่การเป็นพลเมืองโลกของนักเรียนชั้นมัธยมศึกษาปีที่ 1เครือข่ายชาติตระการ 1 พบว่าผลการพัฒนาทักษะการคิดวิเคราะห์เพิ่มขึ้นจากระดับพอใช้ไปสู่ระดับดี และนักเรียนมีความเข้าใจเกี่ยวกับความเป็นพลเมืองโลกเพิ่มมากขึ้น พร้อมยังตระหนักถึงบทบาทของตนเองในการรักษาสิ่งแวดล้อมและมีความรับผิดชอบต่อสังคม This research aims to 1) Study the current status of learning management on the topic of Asian geography for Mathayom 1 students in the Chattrakan Network 1, and 2) Develop a game-based learning activity on Asian geography to enhance analytical thinking skills and foster global citizenship among Mathayom 1 students. The target groups for this study include 1) 4 teachers from opportunity expansion schools in the Chattrakan District 1 School Network Group, under the Office of the Primary Educational Service Area 3, Phitsanulok, in the 2024 academic year, selected through purposive sampling based on specific qualifications, 4 people 2) 11 Mathayom 1 students from BanHuayThongFan School, an opportunity expansion school in the Chattrakan District 1 School Network Group, under the Office of the Primary Educational Service Area 3, Phitsanulok, in the 2024 academic year, selected through purposive sampling based on specific qualifications. The research instruments used in this study consisted of 1) An interview form for teachers instructing the topic of Asian geography for Mathayom 1 students. 2) A game-based learning activity manual on Asian geography for Mathayom 1 students and 3) An analytical thinking skills assessment and behavioral observation. And the statistical methods used in this research include percentage, mean, and standard deviation. The research findings revealed that 1) The current state of learning management in Asian geography for Mathayom 1 students in the Chattrakan Network 1, the existing social studies, religion, and culture curriculum was found to be appropriate for Mathayom 1 students, providing a solid foundation for their learning and future development. In terms of instructional management, it was suggested that teachers should incorporate a variety of teaching strategies and use appropriate instructional media to effectively deliver the content. For learning assessment and evaluation, the study indicated that a range of assessment tools should be utilized to better understand students’ knowledge levels and skills. However, challenges in learning management were identified, including students' lack of concentration and interest in the lesson due to the large amount of content and the absence of a clear and engaging presentation. 2) The development of game-based learning activities, the results showed that using games as a foundation to enhance analytical thinking skills and foster global citizenship among Mathayom 1 students in the Chattrakan Network 1 led to significant improvements. Students’ analytical thinking skills increased from a fair level to a good level. Additionally, students demonstrated a better understanding of global citizenship, becoming more aware of their roles in environmental conservation and showing greater social responsibility.